Thermal behaviour of autoclaved aerated concrete exposed to fire. (September 2015) - Ghazi Wakili, K.; Hugi, E.; Karvonen, L.; Schnewlin, P.; Winnefeld, F.
Abstract: The reaction to fire of autoclaved aerated concrete (AAC) has been investigated at multiple dimensional scales. Changes in the chemical composition were detected and analysed by means of thermal analysis methods. Then, the thermal conductivity after different heat treatments was measured at different temperatures ranging from 120 °C to 720 °C. Finally, the evolution of temperature in an AAC wall exposed to the standard fire of ISO 834 has been monitored by built-in temperature sensors. The results hereof were used as input for a transient and non-linear numerical model which has been set up to predict temperatures at different depths of the wall. Measured and calculated results have been compared and discussed.